Challenges Faced and Coping Strategies Adopted by Nursing Students in Psychiatric Ward - Hange, Archana; Khare, Sumit (Innovational: Journal of Nursing and Healthcare, 2024)
Mental illness is devastating disorders. Unfortunately, this diagnosis is not well understood by the public. Often, those who have mental illness are stigmatized as being “crazy;” “mad;” and millions of them suffer in silence. There are reports of increase in mental illness across the country. These increases have serious implications for psychiatric nursing as more persons are diagnosed with mental illness, the greater the need for psychiatric nurses. Clinical learning plays an important role in nursing education, as it provides opportunities for student nurses to apply the theory learned in the classroom to the real world of clinical nursing. It is also a socialization process through which student nurses are inducted into the practices, expectations, and real-life work environment of the nursing profession. Clinical education is a vital component of psychiatric nursing science, as it provides student nurses with the opportunity to combine cognitive, psychomotor, and affective skills, thus gaining knowledge, skills, and experience in the clinical psychiatric learning environment. Reviewers search nine databases for systematic reviews published in English language peer-reviewed journal between 2010 and 2020. Systematically, the search of significant articles was carried out in various search engines with the following key word: “Coping,” “Adaptation,” and “coping strategies” from the search. Among them, 30 were evaluated to be higher quality. Studies recruiting samples of nursing students posted in psychiatric ward. The findings conclude that majority of students who were posted in the psychiatric ward had moderate level of coping strategies to adapt and work in the psychiatric ward.